1989
DOI: 10.1111/j.1399-6576.1989.tb02867.x
|View full text |Cite
|
Sign up to set email alerts
|

Low–flow anaesthesia does not increase the risk of microbial contamination through the circle absorber system

Abstract: In the circle absorber system, a decrease in fresh gas flow means a higher degree of rebreathing, and, consequently, a higher temperature and humidity within the system. With our present hygienic routines, the circle system tubings are changed and decontaminated once daily. Thus, the same circle system is used for several patients each day. In order to evaluate whether the risk of bacterial contamination increased with the introduction of low-flow anaesthesia, 122 patients anaesthetized with either a low-flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The contact between the gases and the bacteria was performed in liquid at 37°C, which corresponds to clinical conditions and gives optimal conditions for bacterial growth. Soda lime was not used in the circuit because of its controversial bactericidal effects [5,7]. Furthermore, it is known that soda lime is a carbon dioxide absorbant and the use of soda lime is not necessary in clinical pediatric anesthesia practice, unless carbon dioxide is present in the anesthetic circuit.…”
Section: Introductionmentioning
confidence: 99%
“…The contact between the gases and the bacteria was performed in liquid at 37°C, which corresponds to clinical conditions and gives optimal conditions for bacterial growth. Soda lime was not used in the circuit because of its controversial bactericidal effects [5,7]. Furthermore, it is known that soda lime is a carbon dioxide absorbant and the use of soda lime is not necessary in clinical pediatric anesthesia practice, unless carbon dioxide is present in the anesthetic circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly during low-flow anaesthesia, when increased temperature and humidity within the circle system occurs, the risk of endoluminal bacterial growth during prolonged use of ABC has to be considered, as the CO2-absorber might provide a very hostile environment for microorganisms. After 1 day of use, Bengtson et al 29 found a few positive bacteria cultures in the circle system regardless of fresh-gas flow. Our microbiological results were obtained in ABC applied for low-flow anaesthesia; samples obtained from the y-piece and the water trap indicated no difference in the rate of endoluminal contamination of ABC after 1 day compared to 7 days of use.…”
Section: Discussionmentioning
confidence: 99%
“…The fresh gas was air and oxygen; we avoided nitrous oxide because of a possible bias in interpretation [18]. Soda lime was not included in the circuit because of its controversial bactericidal effects [19,20]. Isoflurane was delivered at a concentration equivalent to a MAC of 1.5, which is a normal clinical concentration in air and which is also the concentration at which there are effects on the immune system [8,9,18].…”
Section: Discussionmentioning
confidence: 99%